A Synthetic Approach to Stop-Codon Scanning Mutagenesis - Nie, Lihua (2011)
A general combinatorial mutagenesis strategy using common DMT-protected mononucleotide phosphoramidites and a single orthogonally-protected trinucleotide phosphoramidite (Fmoc-TAG) was developed to scan a gene with the TAG amber stop codon with complete synthetic control. In combination with stop-codon suppressors that insert natural (e.g., alanine) or unnatural (e.g., p-benzoylphenylalanine or Bpa) amino acids, a single DNA library can be used to incorporate different amino acids for diverse purposes. Here, we scanned TAG codons through part of the gene for a model four-helix bundle protein, Rop, which regulates the copy number of ColE1 plasmids. Alanine was incorporated into Rop for mapping its binding site using an in vivo activity screen, and subtle but important differences from in vitro gel-shift studies of Rop function are evident. As a test, Bpa was incorporated using a Phe14 amber mutant isolated from the scanning library. Surprisingly, Phe14Bpa Rop is weakly active, despite the critical role of Phe14 in Rop activity. Bpa is a photoaffinity label unnatural amino acid that can form covalent bonds with adjacent molecules upon UV irradiation. Irradiation of Phe14Bpa-Rop, which is a dimer in solution like wild-type Rop, results in covalent dimers, trimers and tetramers. This suggests that Phe14Bpa Rop weakly associates as a tetramer in solution and highlights the use of Bpa crosslinking as a means of trapping weak and transient interactions.